Preclinical Multimodal Molecular Imaging Using 18F-FDG PET/CT and MRI in a Phase I Study of a Knee Osteoarthritis in In Vivo Canine Model. (20th March 2017) - Menendez, Maria I.; Hettlich, Bianca; Wei, Lai; Knopp, Michael V.
The aim of this study was to use a multimodal molecular imaging approach to serially assess regional metabolic changes in the knee in an in vivo anterior cruciate ligament transection (ACLT) canine model of osteoarthritis (OA). Five canine underwent ACLT in one knee and the contralateral knee served as uninjured control. Prior, 3, 6, and 12 weeks post-ACLT, the dogs underwent 18 F-fluoro-d -glucose ( 18 F-FDG) positron emission tomography (PET)/computed tomography (CT) and magnetic resonance imaging (MRI). The MRI was coregistered with the PET/CT, and 3-dimensional regions of interest (ROIs) were traced manually and maximum standardized uptake values (SUVmax ) were evaluated. 18 F-fluoro-d -glucose SUVmax in the ACLT knee ROIs was significantly higher compared to the uninjured contralateral knees at 3, 6, and 12 weeks. Higher 18 F-FDG uptake observed in ACLT knees compared to the uninjured knees reflects greater metabolic changes in the injured knees over time. Knee 18 F-FDG uptake in an in vivo ACLT canine model using combined PET/CT and MRI demonstrated to be highly sensitive in the detection of metabolic alterations in osseous and nonosteochondral structures comprising the knee joint. 18 F-fluoro-d -glucose appeared to be a capable potential imaging biomarker for early human knee OA diagnosis, prognosis, and management.